The Role of Medial Prefrontal Cortex in Acupuncture Treatment for Functional Dyspepsia - Teng, Yuke; Yin, Tao; Yang, Yue; Sun, Ruirui; Tian, Zilei; Ma, Peihong; He, Zhaoxuan; Qu, Yuzhu; Huang, Liuyang; Chen, Yuan; Zeng, Fang (Frontiers in Neuroscience, 2022)
The effects of acupuncture treating for Functional Dyspepsia (FD) are thought to be related to changes in functional cerebrum activity. This study aimed to reveal the brain response patterns of acupuncture treating for FD. Firstly, this study demonstrated that the changes of brain function activity after acupuncture treatment in 115 FD patients and analyzed the correlation between brain function activity change values and clinical improvement values. Secondly, 115 subjects were divided into acupuncture higher response group and lower response groups based on the median clinical improvement values. Subsequently, changes of functional brain activity after acupuncture treatment were investigated separately in both groups. Finally, brain regions associated with clinical improvement values were used as regions-of-interest (ROI) and resting-state Functional Connectivity (rsFC) comparisons with whole brain voxels were performed. The results demonstrated that the functional activities of the right Medial Prefrontal Cortex (mPFC), left Cerebellum Inferior (CI), right Middle Temporal Gyrus (MTG) decreased, and increased in the left Heschl and right Middle Cingulate Cortex (MCC) in 115 FD patients after acupuncture treatment. The functional connectivity changes of mPFC were correlated with the improvement value of Nepean Dyspepsia Symptom Index (NDSI). The significant decrease in MPFC functional activity was found in acupuncture higher response FD patients, but not in lower response FD patients. The functional connectivity between MPFC and Default Mode Network (DMN) was significantly enhanced in the higher response group. In conclusion, this study suggested that modulating the functional activity of the MPFC and the pattern of its associated DMN are one of important mechanisms of acupuncture for treating FD.